Herbarium specimens provide reliable estimates of phenological responses to climate at unparalleled taxonomic and spatiotemporal scales. Issue 10 (18th August 2022) - Ramirez‐Parada, Tadeo H.; Park, Isaac W.; Mazer, Susan J.
Abstract : Understanding the effects of climate change on the phenological structure of plant communities will require measuring variation in sensitivity among thousands of co‐occurring species across regions. Herbarium collections provide vast resources with which to do this, but may also exhibit biases as sources of phenological data. Despite general recognition of these caveats, validation of herbarium‐based estimates of phenological sensitivity against estimates obtained using field observations remains rare and limited in scope. Here, we leveraged extensive datasets of herbarium specimens and of field observations from the USA National Phenology Network for 21 species in the United States and, for each species, compared herbarium‐ and field‐based estimates of peak flowering dates expected under standardized temperature conditions, and of sensitivity of peak flowering time to geographic and interannual variation in mean minimum temperatures (TMIN). We found strong agreement between herbarium‐ and field‐based estimates for standardized peak flowering time (r = 0.91, p < 0.001) and for the direction and magnitude of sensitivity to both geographic TMIN variation (r = 0.88, p < 0.001) and interannual TMIN variation (r = 0.82, p < 0.001). This agreement was robust to substantial differences between datasets in 1) the long‐term TMIN conditions observed among collection and phenological monitoring sites and 2) the interannual TMIN conditions observed in the time periods encompassed by both datasets for most species. Our results show that herbarium‐based sensitivity estimates are reliable among species spanning a wide diversity of life histories and biomes, demonstrating their utility in a broad range of ecological contexts, and underscoring the potential of herbarium collections to enable phenoclimatic analysis at taxonomic and spatiotemporal scales not yet captured by observational data.